ANALISIS HUBUNGAN PERILAKU BERISIKO TERHADAP RISIKO KEJADIAN DIABETES MELLITUS TIPE 2 PADA REMAJA - Santoso, Raden Bagus Edy; Noorma, Nilam; MS, Dewi Sartika; Setyowati, Tutik (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Adolescents who are at a productive age today are increasingly vulnerable to the risk of degenerative diseases, especially type 2 diabetes mellitus, due to unhealthy lifestyles. Based on an initial survey conducted by researchers on adolescents in several high school interviews, 7 out of 10 students have the behavior of often eating fast food or junk food, 9 out of 10 students drink sweet drinks such as iced tea more than once a day, 6 out of 10 students lack physical activity every day, and 3 out of 10 students have a history of Diabetes Mellitus with GDA ≥140 ml/dl. The purpose of the study was to analyze the relationship of risky behavior to the risk of developing type 2 diabetes mellitus in adolescents. The research design used in this study was cross sectional. The research was conducted in 5 high schools in Samarinda City. The research was conducted in September 2024. The population was all high school students in 5 high schools in Samarinda City. The sample amounted to 57 respondents. The sampling technique used Simple Random Sampling. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed a relationship between risky behavior (p value: 0.000) and the incidence of diabetes mellitus in adolescents. It is recommended for adolescents to increase physical activity, maintain a healthy diet by limiting fast food.Keywords: Diabetes Mellitus, Risk Behavior, Adolescents.